PEMBELAJARAN FISIKA BERBASIS PROYEK TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN KOLABORATIF PESERTA DIDIK - Martar, Egha (Jurnal Citra Pendidikan, 2024)
This research was conducted to determine the effect of implementing learning usingprojects on students' critical and collaborative thinking abilities. Critical thinking skillsare a thinking process that allows someone to evaluate or examine the evidence,assumptions and logic behind other people's ideas. The ability to collaborate is one of theabilities developed in the 21st century. Collaboration in learning has a mediating rolebetween interactivity abilities and learning achievement because active collaborativelearning is a media link between interactivity and learning achievement. Apart from that,this research was also motivated by the low critical and collaborative thinking abilities ofstudents in the learning process. This is because students are not encouraged to developtheir thinking abilities and learning in class is only directed at memorizing informationwithout being required to understand what they remember